Widespread specific intron retention events in nuclear RNA complexes identified by sedimentation analysis of pluripotent cellular extracts - Pereira, Isabela T.; Mamede, Izabela; Amaral, Paulo P.; Franco, Gloria R.; Rinn, John L. (Genome Research, 2025)
Many essential cellular processes require RNA to interact with protein(s) to form ribonucleic protein complexes (RNPs). For example, all cellular proteins are produced by the ribosome, a large and stable RNP. Gene splicing requires a choreography of numerous small and large RNPs; even the replication of telomeric DNA requires an RNP. All these examples are stable RNPs that exhibit specific sedimentation rates (e.g., in a sucrose gradient) based on the composition of RNA and protein. In this study, we aimed to identify RNA components of discrete RNPs on a transcriptome-wide scale. Using sucrose gradient sedimentation followed by sequencing, we identified 1057 RNA transcripts, both coding and noncoding, that are likely to be components of cellular RNPs. We named these transcripts gradient-enriched transcripts (GETs). GETs were predominantly nuclear, metabolically stable, and they were not the major splice isoforms, but instead they were mostly retained-intron isoforms, each containing a specific retained intron, and this intron retention phenomenon is conserved in humans and mice. Collectively, our study reveals a widespread phenomenon of a specific intron being retained in a stable nuclear RNPs.